The Role of English as a Foreign Language Teachers’ Mindfulness and Compassion in Fostering Students’ Foreign Language Enjoyment - Huang, Jingjing (Frontiers in Psychology, 2022)
With the popularity of positive psychology in English as a Foreign Language (EFL) teaching and learning, learners’ positive emotions have attracted great academic attention. Foreign language enjoyment (FLE) is regarded as a constructive emotion and key component for learners’ academic engagement that is affected by educators’ emotions and psychological attributes. Earlier studies have proved the positive role of educators’ mindfulness and compassion in reducing learners’ negative feelings, boosting their positive emotions and building a harmonious teacher-student rapport. Through mindful and compassionate training, EFL teachers are skilled at creating a joyful learning atmosphere, showing understanding and support towards learners, as well as inspiring learners with enthusiasm and joy. The present review makes efforts to emphasize the significant effect of EFL teachers’ mindfulness and compassion on fostering students’ FLE. Moreover, a number of practical implications are provided for EFL teachers, teacher educators, school managers, and future directions are offered for enthusiastic researchers to conduct similar and complementary research in the field of foreign language education.